Alpheus dentipes Guerin-Meneville 1832 ... - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
** Alpheus dentipes Guérin-Méneville, 1832 An eastern Atlantic and Mediterranean species of which a single, small specimen was recorded from Portland Bay (present day Islas Canning), western Patagonia by Miers (1881, as Alpheus sp.) and identified by Coutière (1899) as A. dentipes; possibly mislabelled (see Holthuis 1952) or potentially a mis-identification of the more northern, extra-limital Alpheus inca Wicksten & Méndez, 1981. ... : Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 222, DOI: 10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302 ...